Control of gluconeogenesis by isocitrate lyase in endosperm of germinating castor bean seedlings - Runquist, M; Kruger, N (1999)
The aim of this work was to quantify the contribution of isocitrate lyase to the control of gluconeogenesis in endosperm from 4-day-old castor bean seedlings. The approach was based on metabolic control analysis following selective inhibition of enzyme activity. Both 3-nitropropionate and itaconate decreased the proportion of either [1-14C]acetate or [2-14C]acetate converted to sucrose, and increased the proportion metabolized through the tricarboxylic acid cycle. Kinetic analysis of isocitrate lyase activity from endosperm revealed that itaconate is a pure uncompetitive inhibitor (K(i)' = 11.9 ± 0.98 μM) with respect to isocitrate. In contrast, 3-nitropropionate is a slow, tight-binding inhibitor. The half-time for inhibition of isocitrate lyase by 3-nitropropionate was 5-10 min, whereas the half-time for reactivation was in excess of 10 h. Incubating endosperm in 3-nitropropionate resulted in a concentration-dependent decrease in isocitrate lyase activity that remained stable in tissue extracts for at least 4 h. From a comparison of the extent of in situ inactivation of isocitrate lyase by 3-nitropropionate and the effect of this compound on the rate of sucrose production from [2-14C]acetate, the flux control coefficient of isocitrate lyase on gluconeogenesis from acetate in castor bean endosperm was calculated to be 0.66 ± 0.09. It is concluded that isocitrate lyase activity is quantitatively important in the control of gluconeogenic flux, and suggested that developmental changes in the amount of this enzyme may be an important factor in determining the conversion of lipid to sugar in young castor bean seedlings.